Integrasi Pengembangan Spiritual Pada Psikologi Pendidikan: Pendekatan Jalaluddin Rumi Dalam Meningkatkan Prestasi Siswa - Priyono, Cipto Duwi; Pebriyenni, Pebriyenni; Enjoni, Enjoni; Wandi, Joni Indra; Afnita, Nora (Affection: Journal of Psychology And Counseling, 2024)
Education is an inevitable effort in shaping individuals into quality human beings, yet often spirituality is sidelined. In this research, we explore the integration of spiritual development in education using the Rumi approach and its impact on student achievement. Through literature review, we found that this approach significantly influences student achievement. Integrating spiritual values into the curriculum enhances students' intrinsic motivation, happiness in learning, and mental resilience. The findings highlight the importance of integrating spiritual development in education to enhance overall student achievement. Practical implications of this research include the need for curriculum renewal, teacher training, and school environments that support holistic spiritual growth of students. These steps are crucial to ensure that education not only shapes intellectual intelligence but also nurtures balanced individuals holistically.